If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7v + -40 = 9(v + -8) Reorder the terms: -40 + -7v = 9(v + -8) Reorder the terms: -40 + -7v = 9(-8 + v) -40 + -7v = (-8 * 9 + v * 9) -40 + -7v = (-72 + 9v) Solving -40 + -7v = -72 + 9v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-9v' to each side of the equation. -40 + -7v + -9v = -72 + 9v + -9v Combine like terms: -7v + -9v = -16v -40 + -16v = -72 + 9v + -9v Combine like terms: 9v + -9v = 0 -40 + -16v = -72 + 0 -40 + -16v = -72 Add '40' to each side of the equation. -40 + 40 + -16v = -72 + 40 Combine like terms: -40 + 40 = 0 0 + -16v = -72 + 40 -16v = -72 + 40 Combine like terms: -72 + 40 = -32 -16v = -32 Divide each side by '-16'. v = 2 Simplifying v = 2
| (39200+-8x)=-770 | | 2(w+9)=7w-2 | | 8(4900-x)=770 | | 8v-7=-3(v+6) | | -6x+5.4=6.3+1.2x | | x/3=15/2 | | (1/(ab))/(1/(ab^2))/(1/(a^2b)) | | 2x(x+3)=-15 | | 216=45t | | x^4(a-b)+16(b-a)=0 | | 0.30x+0.05(20-x)=0.10(-10) | | Log(x^2-9)-3=log(x+3) | | 1/2w-2/3=2/3 | | H*t=128t-16t^2 | | 3x/9x= | | 9-5/2= | | (5x-6)(2x+9)= | | 0=-0.125x^2+0.35x+0.75 | | 4(x-2)4x+10= | | Log(x^2-9)-log(x+3)=3 | | y=-0.125x^2+0.35x+0.75 | | -2v+34=8(v+3) | | (4x^2-3x^3)-(8x^2-5x^3)= | | 17z-6z+3= | | 5w^2-3w=17 | | 9x^2/lnx | | 8(u+4)=-2u+12 | | 100=-0.1x+1 | | x^2-12x+36=352 | | -3x=12x+-8+1 | | 3=-0.1x+1 | | 45=-0.1x+1 |